Thromboembolism and Bleeding Tendency in Congenital Factor XII DeficienCy - A Study on 74 Subjects from 14 Swiss Families - Lämmle, Bernhard; Wuillemin, Walter A; Huber, Isabelle; Krauskopf, Marina; Zürcher, Christian; Pflugshaupt, Rolf; Furlan, Miha (Thrombosis and Haemostasis, 1991)
In order to assess the clinical implications of hereditary F XII deficietrcy, all available members of Swiss families with F XII deficiency were investigated. Based on the F XII: C values and the family pedigree, the 74 subjects, aged 8-–82 years, were classified as homozygotes/double heterozygotes for F XII deficiency (n = 18), as obligatory (n = 20) or possibly (n = 25) heterozygotes, respectively, and as norrnals (n = 11). None of the 18 subjects with F XII: C <0.01 U/ml and only one possibly heterozygous woman had an abnormal bleeding tendency, confirming the notion that Hageman trait generally does not result in a hemorrhagic diathesis. Two of the 18 subjects with severe F XII deficiency had suffered from venous thromboembolic disease at age <40 years. One heterozygous woman had a leg ulcer probably due to venous thrombosis. Thus, whereas homozygous F XII deficiency may be associated with an increased risk for venous thromboembolic disease, partial F XII deficiency is not, by itself, a strong risk factor for thrombosis.Where as 17 of the 18 subjects with F xII : C <0.01 U/ml had no detectable F XIL Ag, one cross reacting material-positive F XII deficient subject (F XII:Ag = 0.11 U/ml) was identified. The dysfunctional F XII, present in this subject's plasma and tentatively called F XII Bern, is the fourth abnormal F XII molecule identified so far.